Investigation of the inhibitory potential of secondary metabolites isolated from Fernandoa adenophylla against Beta-glucuronidase via molecular docking and molecular dynamics simulation studies - Abdur Rauf; Rahaf Ajaj; Zuneera Akram; Majid Khan; Abdul Wadood; Maryam Zulfat; Zafar Ali Shah; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani; Humaira Hussain; Dorota Formanowicz (PLoS ONE, 2025)
Elevated β-glucuronidase activity is associated with the production of toxic metabolites that contribute to tumor development and other diseases. Inhibiting this enzyme may offer therapeutic potential, including the prevention of colonic carcinogenesis. This study investigates the antidiabetic potential of metabolites derived from Fernandoa adenophylla, using β-glucuronidase as a model enzyme linked to hyperglycemia. Both Escherichia coli and human isoforms of β-glucuronidase were evaluated. Among the tested compounds, AA and DD exhibited the most significant inhibitory activity against the E. coli isoenzyme, with inhibition rates of 85.2% (IC₅₀ = 12.3 µM) and 82.6% (IC₅₀ = 8.2 µM), respectively. Against the human isoenzyme, compounds DD and CC showed the highest inhibition, with 92.6% (IC₅₀ = 28.2 µM) and 90.4% (IC₅₀ = 8.9 µM), respectively. These findings were further supported by molecular docking and molecular dynamics simulations. So, these results highlight the potential of F. adenophylla metabolites as promising candidates for developing novel therapeutic agents targeting β-glucuronidase.